An Uncommon Presentation of Chronic Lymphocytic Leukemia: Bilateral Hearing Loss - Erikci, Alev Akyol; Öztürk, Ahmet; Sayan, Ozkan (Fırat University, 2007)
Sudden sensorineural hearing loss that presents as the initial sign of haematological disease is very rare. We report a case with typical Rai Stage 2 (Binet Stage A) CLL, who presented with sudden onset deafness as the initial manifestation. A 48-year-old male presented with sudden bilateral sensorineural hearing loss. The patient was found to have chronic lymphocytic leukemia (CLL) during a work-up for his hearing loss. Early onset of sudden deafness in a CLL patient may be due to the hyperviscosity syndrome. Audiograms were recorded showing positive findings on presentation and recovery after therapy. The importance of early diagnosis and therapy is stressed in the light of this rapid clinical and audiological recovery observed here. ©2007, Firat University, Medical Faculty

Ani işitme kaybı hematolojik hastalıklarda nadiren bir başvuru belirtisi olabilir. Burada başvuru nedeni ani işitme kaybı olan Rai evre 2 (Binet evre A) olan kronik lenfositik lösemi (KLL) vakasını sunmaktayız. Kırk sekiz yaşındaki erkek hasta bilateral işitme kaybı ile başvurdu. İşitme kaybının nedeni araştırılırken KLL tespit edildi. Tedavi öncesine göre odiyogramlarında belirgin düzelme elde edildi. Ani işitme kaybı hiperlökositozun yol açtığı lökostaz ile ilişkilendirildi. İşitsel düzelimin ışığında erken tanı ve tedavinin önemi vurgulandı. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Kronik Lenfositik Lösemide Nadir Bir Başvuru Şekli: Bilateral İşitme Kaybı